Neuronal Activity in the Caudal Frontal Eye Fields of Monkeys during Memory-Based Smooth Pursuit Eye Movements: Comparison with the Supplementary Eye Fields - Fukushima, Junko (Oxford University Press, 2011)
Recently, we examined the neuronal substrate of predictive pursuit during memory-based smooth pursuit and found that supplementary eye fields (SEFs) contain signals coding assessment and memory of visual motion direction, decision not-to-pursue (“no-go”), and preparation for pursuit. To determine whether these signals were unique to the SEF, we examined the discharge of 185 task-related neurons in the caudal frontal eye fields (FEFs) in 2 macaques. Visual motion memory and no-go signals were also present in the caudal FEF but compared with those in the SEF, the percentage of neurons coding these signals was significantly lower. In particular, unlike SEF neurons, directional visual motion responses of caudal FEF neurons decayed exponentially. In contrast, the percentage of neurons coding directional pursuit eye movements was significantly higher in the caudal FEF than in the SEF. Unlike SEF inactivation, muscimol injection into the caudal FEF did not induce direction errors or no-go errors but decreased eye velocity during pursuit causing an inability to compensate for the response delays during sinusoidal pursuit. These results indicate significant differences between the 2 regions in the signals represented and in the effects of chemical inactivation suggesting that the caudal FEF is primarily involved in generating motor commands for smooth-pursuit eye movements.